PELATIHAN GURU SEKOLAH DASAR PADA MODEL PEMBELAJARAN KURIKULUM 2013: PRO DAN KONTRA - Mislinawati Mislinawati; Suci Fitriani (Jurnal Pesona Dasar, 2021)
Most of teachers in Aceh have not applied innovative teaching models as suggested in the Curriculum 2013. Generally they teach without using curriculum models suggested in the 2013 curriculum. Teachers are not yet fully informed about the learning models, so teachers are difficulty and rarely apply in the learning process. Based on the problems experienced by these teachers, then the thing done to solve the problem is to provide training and mentoring activities. Subjects in this study teachers SDN Banda Aceh as many as 40 people. This study employed descriptive qualitative method. Training on the learning model based on the 2013 curriculum for two days includes: first day of theoretical training on learning model; The second day, the training to practice the learning model that will be developed. Further assistance in developing and practicing the model of learning in the classroom for four months. In the process of mentoring teachers guided from the process of making learning tools such as RPP, Media and LKS. The results showed that only 30% applied the models suggested in the curriculum 2013. Teachers' efforts in applying these models are demonstrated by the teacher's persistence from the process of making the lesson plan, it seems that the teachers who applied the models were enthusiastic in fixing model-based RPPs, looking at modules, designing the required media, and asking actively when something is poorly understood. Teachers are recommended to apply the 2013 curriculum learning models in order to have innovative classroom activities that can make the students active and enthusiastic.